Predicting Social Adjustment Based on Academic Performance and Academic Self-Concept in Children of Single Parents - Yousefi, Ensiyeh; Gholampour, Parsa; Nabavi, Nasrin; Chopani, Mohammadreza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The current study aimed to predict social adjustment based on academic performance and academic self-concept in children of single parents.Methods and Materials: This research was applied and descriptive-correlational in nature. The study population consisted of all students (ages 12 to 15) in Sanandaj during the academic year (2020-2022), among whom 200 students were selected using a purposive sampling method. For data collection, the Pekl and Weisman Social Adjustment Questionnaire (1999), the Salehi Academic Performance Questionnaire (2015), and the Yes Yesen Chen Academic Self-Concept Questionnaire (2004) were used. For inferential statistics analysis, simultaneous multiple regression was performed using SPSS version 23.Findings: The findings indicated that the t-test for significance in regression for both academic performance and academic self-concept was significant at the level of less than 0.01. Additionally, academic performance and academic self-concept could explain 37.1% of the variance in social adjustment. Therefore, based on the components of academic performance and academic self-concept in children of single parents, their social adjustment can be predicted.Conclusion: Given the findings of this research on the relationship between social adjustment and both academic performance and academic self-concept, it is essential for educational interventions and counseling to consider the level of social adjustment among psychologists and educational counselors.